Evaluation Of The Mannheim Peritonitis Index In Patients With Perforation Peritonitis - Prajapati, Ijendra; Bharti, Shiv Vansh; Sharma, Anup; Dhakal, Sunil (Journal of Society of Surgeons of Nepal, 2024)
Introduction: Perforation peritonitis is a common cause of emergency admissions in the surgery department, posing significant diagnostic and management challenges. Various scoring systems have been developed to objectively assess patients' conditions at different stages of the disease. At Nepalgunj Medical College Teaching Hospital, Kohalpur, patients with perforation peritonitis from two provinces are frequently encountered, but there has been no study on their morbidity and mortality. Recognizing the need for an accurate and straightforward assessment system, this study aimed to evaluate patients with perforation peritonitis using the Mannheim Peritonitis Index. Methods: This clinical, prospective, observational study was conducted at Nepalgunj Medical College Teaching Hospital, Kohalpur, from May 2017 to April 2018. It involved 70 patients who underwent emergency exploratory laparotomy for perforation peritonitis. Data on patient details, diagnosis, investigations, and surgical procedures were collected using a case recording form and analyzed using statistical methods such as mean, standard deviation, proportions, percentages, and chi-square tests where applicable. Results: This study involved 70 cases of non-traumatic hollow viscus perforation peritonitis, with a mean patient age of 45.5±15.5 years (range 17–76). Peptic ulcer perforation was the most common cause, accounting for 49% of cases. Mortality rates were 0%, 12.9%, and 40% for MPI scores of <21, 21-29, and >29, respectively. Statistically significant risk factors for mortality included organ failure (p=0.010), cause of peritonitis (p=0.008), origin of sepsis (p=0.0000), and exudate character (p=0.017). The Mannheim Peritonitis Index (MPI) showed reliable sensitivity (80%), specificity (78.3%), and accuracy (78%). Wound infection was the most common morbidity. Conclusion: The Mannheim Peritonitis Index (MPI) is a simple and effective tool for stratifying and predicting mortality in patients with peritonitis due to hollow viscous perforation. However, the MPI score was not significant in predicting morbidity in these patients.